Pelatihan Parenting Melalui Pemanfaatan Internet Sehat Sebagai Upaya Mengurangi Kecanduan Internet (Media Sosial) Pada Yayasan Nurul Islam Sabillurrosyad - Agustiena Merdekawati; Azis Sukma Dhiana; Jefina Tri Kumalasari; Irwin Sukrisno Sugeng; Susi Wahyu Lestari (Jurnal Pengabdian kepada Masyarakat Radisi, 2021)
Digital parenting is a parenting strategy related to the rules for using digital devices both online and offline to protect children's safety from the threats of their use. This community service is to provide parenting training through the use of healthy internet as an effort to reduce internet addiction (social media) so that they can socialize how to use internet media and social media properly and correctly, disseminate information and education and guide them to be more careful in choosing their use. good and right and responsible internet, so it doesn't make social media addiction. In this training activity, it was held at the Nurul Islam Sabillurrosyad Foundation with a target for housewives and students. The implementation method for the activity is providing parenting socialization and training through the use of healthy internet to reduce internet addiction (social media), conducting questions and answers and discussions with sharing experiences.